Extracellular matrix networks in bone remodeling. (August 2015) - Alford, Andrea I.; Kozloff, Kenneth M.; Hankenson, Kurt D.
Abstract: Bones are constantly remodeled throughout life to maintain robust structure and function. Dysfunctional remodeling can result in pathological conditions such as osteoporosis (bone loss) or osteosclerosis (bone gain). Bone contains 100s of extracellular matrix (ECM) proteins and the ECM of the various bone tissue compartments plays essential roles directing the remodeling of bone through the coupled activity of osteoclasts (which resorb bone) and osteoblasts (which produce new bone). One important role for the ECM is to serve as a scaffold upon which mineral is deposited. This scaffold is primarily type I collagen, but other ECM components are involved in binding of mineral components. In addition to providing a mineral scaffolding role, the ECM components provide structural flexibility for a tissue that would otherwise be overly rigid. Although primarily secreted by osteoblast-lineage cells, the ECM regulates cells of both the osteoblast-lineage (such as progenitors, mature osteoblasts, and osteocytes) and osteoclast-lineage (including precursors and mature osteoclasts), and it also influences the cross-talk that occurs between these two oppositional cells. ECM influences the differentiation process of mesenchymal stem cells to become osteoblasts by both direct cell-ECM interactions as well as by modulating growth factor activity. Similarly, the ECM can influence the development of osteoclasts from undifferentiated macrophage precursor cells, and influence osteoclast function through direct osteoclast cell binding to matrix components. This comprehensive review will focus on how networks of ECM proteins function to regulate osteoclast- and osteoblast-mediated bone remodeling. The clinical significance of these networks on normal bone and as they relate to pathologies of bone mass and geometry will be considered. A better understanding of the dynamic role of ECM networks in regulating tissue function and cell behavior is essential for the development of new treatment approaches for bone loss.